To see only shadows. - Office Building; Elo, Teemu; Käppi, Pekko; Laurila, Janne; Leinonen, Ville, 1975-; Sänpäkkilä, Sami, 1975-; Vierimaa, Mika; Fonal Records (Ulvila : Fonal Records, 2000)
8 kappaletta.
To see only shadows -- Lighthouse girl -- One-eighty -- It all comes down on you -- Crazy and ridiculous -- The driver -- You right here, whenever -- Cut my heart in two.
Laulujen sanat tekstiliitteessä.
Office Building: Janne Laurila, Ville Leinonen, Mika Vierimaa, Pekko Käppi, Teemu Elo, Sami Sänpäkkilä.
Office Building (yhtye): Janne Laurila, Ville Leinonen, Mika Vierimaa, Pekko Käppi, Teemu Elo, Sami Sänpäkkilä.
Sanat tekstiliitteessä: englanti.
Puuttuu JYKin kokoelmasta
Keywords: Office Building -- albumit; rock